Strategi Digitalisasi UMKM Warung Kopi Saisuak Melalui Pengembangan Blog Sebagai Media Promosi Di Kota Padang - Desi Ratna Sari; Fauzan Azmi; Nandy Phinto; Rafidola Mareta Riesa; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Web design is the process of designing the user interface and visual experience of a website. It includes various elements such as layout, color, typography, and other graphic elements that affect how users interact with the site. One of the online sites that can be used is a blog. A blog is a type of website or online platform that contains a series of posts or articles that are updated regularly. The digitalization strategy through blogs can expand business reach and increase interaction with users. The method used in designing this blog is data collection through direct observation and interviews with MSME owners. The existence of a website such as a Blog can help small and medium enterprises (SMEs), especially Warung Kopi Saisuak in promoting their food and beverage products online. With this blog site, Warung Kopi Saisuak can be better known and encourage business growth through a dedicated Blogger site.